2017
DOI: 10.3390/cryst7120363
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Liquid on the Outcome of Halogen-Bonded Metal–Organic Materials Synthesis by Liquid Assisted Grinding

Abstract: Abstract:In this work, we describe novel multi-component halogen bonded solids of Co(II) complexes and 1,4-diiodotetrafluorobenzene, 14tfib. We present the important influence of liquid on the outcome of liquid assisted grinding of dichlorobis(1,10-phenantroline)cobalt(II), CoCl 2 (phen) 2 and 14tfib. Grinding of solid reactants with a small amount of water gives the cocrystal product [CoCl 2 (phen) 2 ](14tfib) (1) while grinding with a small amount of methanol gives an ionic structure, the four-component soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…8). 77,78 As a result of using different halogen bond donors, the resulting halogen bonding motifs led to different dimensionalities of the crystal structures, ranging from discrete supramolecular complexes to three-dimensional networks.…”
Section: Crystengcomm Highlightmentioning
confidence: 99%
“…8). 77,78 As a result of using different halogen bond donors, the resulting halogen bonding motifs led to different dimensionalities of the crystal structures, ranging from discrete supramolecular complexes to three-dimensional networks.…”
Section: Crystengcomm Highlightmentioning
confidence: 99%
“…To date, various Lewis bases (neutral molecules or charged species) have been employed as halogen bond acceptors in constructing halogenbonded supramolecular assemblies. These have most commonly been organic [13,14] and metal-organic [15] molecules containing electron-rich nitrogen [16][17][18][19][20][21][22][23][24][25][26] and oxygen atoms [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], as well as inorganic anions such as halogenides [42][43][44][45][46][47][48][49][50][51][52][53][54]. The most commonly used halogen bond donors have traditionally been neutral organic molecules where a halogen atom is bonded to electron-withdrawing molecular residues.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the reaction outcome, depending on whether CuCl 2 ⋅ 2H 2 O or CuCl 2 is used, once more draw attention to the role that water molecules have in co‐crystal synthesis. Previous studies have shown that a liquid phase released from hydrate reactants can enhance [23] and autocatalyze [24] the formation of co‐crystals or, in the case of a metal‐organic system, direct reactions towards the neutral metal‐organic co‐crystal instead of the ionic co‐crystal [15b] . In this case, the presence of hydrate water evidently directs the reaction towards the formation of a co‐crystal containing the mononuclear copper(II) complex, while the absence of hydrate water directs the reaction towards the formation of co‐crystal containing the dinuclear copper(II) complex.…”
Section: Resultsmentioning
confidence: 99%